Re‐evaluation of citric acid esters of mono‐ and diglycerides of fatty acids (E 472c) as a food additive in foods for infants below 16 weeks of age and follow‐up of its re‐evaluation - EFSA Panel on Food Additives and Flavourings (FAF); Laurence Castle; Monica Andreassen; Gabriele Aquilina; Maria Lourdes Bastos; Polly Boon; Biagio Fallico; Reginald FitzGerald; Maria Jose Frutos Fernandez; Bettina Grasl‐Kraupp; Ursula Gundert‐Remy; Rainer Gürtler; et al. (EFSA Journal)
Abstract Citric acid esters of mono‐ and diglycerides of fatty acids (E 472c) was re‐evaluated in 2020 by the Food Additives and Flavourings Panel (FAF Panel) along with acetic acid, lactic acid, tartaric acid, mono‐ and diacetyltartaric acid, mixed acetic and tartaric acid esters of mono‐ and diglycerides of fatty acids (E 472a,b,d,e,f). As a follow‐up to this assessment, the FAF Panel was requested to assess the safety of citric acid esters of mono‐ and diglycerides of fatty acids (E 472c) for its use as food additive in food for infants below 16 weeks of age belonging to food categories (FCs) 13.1.1 (Infant formulae as defined by Directive 2006/141/EC) and 13.1.5.1 (Dietary foods for infants for special medical purposes and special formulae for infants). In addition, the FAF Panel was requested to address the recommendation of the re‐evaluation of E 472c as a food additive to update the EU specifications in Commission Regulation (EU) No 231/2012. For this, a call for data was published to allow interested partied to provide the requested information for a risk assessment. The Panel concluded that the technical data provided by the interested business operators support an amendment of the EU specifications for E 472c. Regarding the safety of the use of E 472c in food for infants below 16 weeks of age, the Panel concluded that there is no safety concern from its use at the reported use levels and at the maximum permitted levels in food for infants below 16 weeks of age (FCs 13.1.1 and 13.1.5.1).